Comment on Mahariq et al. Investigation and Analysis of Acoustojets by Spectral Element Method. Mathematics 2022, 10, 3145; Mathematics; Vol. 10, iss. 23 - Minin I. V. Igor Vladilenovich (2022, 2022)
Title screen